NEUTRALIZING EMOTIONS IN EARLY CHILDREN - Rohmawati, Nina Rizka; Diana, Meli; Riesmiyatiningdyah (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Humans have a characteristic of imitative behavior, including children. Good or bad behavior, good or bad behavior, good or bad habits, are all formed in the social environment (home). Where this can happen due to children's observations of their parents. We must understand the management of emotions in children properly. Because it could be that the emotions conveyed by children are an affirmation or confirmation of the behavior that we as parents exemplify or the application of what we teach. Parents do have more experience than children so they teach their children what they have experienced or know. From the results of the study, it was found that there are still many parents who do not properly capture their children's emotions. So that good emotional management for children has not been achieved. Neutralizing emotions in this child was ultimately chosen as material used for community service activities. With the aim that parents know so they can properly capture their children's emotions. Apart from that, it is also hoped that there will be no incidents of parental violence towards children. This community service was carried out in Rangkah Kidul Village, Sidoarjo. Attended by parents of kindergarten and elementary school students. The activity was carried out in 1 day with a preparation time of 5 weeks. The activity ran smoothly with a total of 56 parents invited and 46 parents attending